Small Research and Asking Questions. a Study Case in Initial Teacher Training in Elementary Education - Joglar-Campos, C (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2019)
In Chile s educational policy, teacher training has been a priority, particularly over the last decade. These pretensions bring with them important challenges and the construction of proposals that take care of them. That is how the promulgation of Ley 20.903 (2016) incorporated new pedagogical and subject standards for all the careers in Pedagogy. In the case of Elementary Pedagogy (future teachers who will take care of the first and second infancy) it is an even more challenging issue, because for the science area it must promote scientific thought competencies, understanding the nature of science, that is its activity and construction of knowledge and doing science. One of the possibilities to undertake this formative responsibility is the use of small research in which asking questions is a key, not only because of its direct relation with learning, but also with scientific activity proper. Under these considerations, this research, in its first stage, of a qualitative character with a case study, had the purpose of characterizing the construction of explicative questions by 65 students in the Understanding of the Natural Medium I and III in their third and fifth semesters of the Basic Pedagogy career of a Chilean state university over an academic semester during the implementation of small research. The results refer mainly to questions meant to be researchable with difficulties in incorporating relations between variables and scientific knowledge. Furthermore, in their content, they are located mainly in phenomena observed from the social and everyday context that represents more biological than chemical and physical models. As to the demand, it is noteworthy that even though teachers prepare more questions to establish relations and confirm them, they are afraid of asking questions that imply predictions. This situation forces to think how to generate a curriculum in science for future teachers that will prioritize the formulation and benefits of the questions if an understanding of the nature of science is desired.